The BLISS study: Beta-Lactam infusion in severe sepsis-randomised controlled trial of continuous versus intermittent beta-lactam infusion in critically ill patients with severe sepsis in a Malaysian ICU setting - Abdul Aziz, Mohd. Hafiz; Sulaiman, Helmi; Mat Nor, Mohd Basri; Rai, Vineya; Wong, K.; Hasan, Mohd Shahnaz; Wallis, Steven C; Lipman, Jeffrey; Staatz, Christine E.; Roberts, Jason A. (2015)
Background: This study aims to determine if continuous infusion (CI) of beta-lactam antibiotics achieves the pharmacokinetic/pharmacodynamic (PK/PD) targets for time-dependent bacterial killing and/or are associated with improved clinical outcomes compared to intermittent bolus (IB) dosing in critically ill patients with severe sepsis. Methods: This is a report from the BLISS Study which was a prospective, multicentre, open-labelled, randomised, controlled trial of CI vs IB dosing of beta-lactam antibiotics, recruiting critically ill patients with severe sepsis from two Malaysian ICUs. The primary end-point, PK/PD target attainment, was evaluated at the halfway point and end of the dosing interval on days 1 and 3 of treatment, by comparing beta-lactam concentrations against causative pathogens based on EUCAST MIC. Secondary end-points were number of days before patient’s white blood cell (WBC) count normalised and that patient’s required infection-related mechanical ventilation (MV), as well as 14-day mortality. Results: 140 critically ill patients with severe sepsis were enrolled with 70 patients each randomly allocated to the CI and IB treatment arms. APACHE II (CI 22 vs IB 20, p = 0.336) and SOFA (CI 9 vs IB 8, p = 0.217) scores were similar between CI and IB patients. CI patients demonstrated numerically higher PK/PD target attainment rates compared to IB patients at the halfway point (CI 96.6% vs IB 83.9%, p = 0.022) and end (CI 96.6% vs IB 62.5%, p < 0.001) of the dosing interval on Day 1, and at the halfway point (CI 100.0% vs IB 85.7%, p = 0.003) and end (CI 98.2% vs IB 58.9%, p < 0.001) of the dosing interval on Day 3, respectively. WBC count normalisation (CI 4 vs IB 6 days, p = 0.014) and infection-related MV (CI 6 vs IB 9 days, p = 0.038) were shorter for CI patients. Mortality rates (CI 17.7% vs IB 16.0%, p = 0.807) were similar between CI and IB patients. Conclusion: Preliminary results of the BLISS study provide additional PK/PD and clinical outcome data to support the practice of CI administration of beta-lactam antibiotics in critically ill patients with severe sepsis.